Mechanisms mediating the impact of maternal obesity on offspring hypothalamic development and later function - Furigo, Isadora C.; Dearden, Laura (Frontiers in Endocrinology, 2022)
As obesity rates have risen around the world, so to have pregnancies complicated by maternal obesity. Obesity during pregnancy is not only associated with negative health outcomes for the mother and the baby during pregnancy and birth, there is also strong evidence that exposure to maternal obesity causes an increased risk to develop obesity, diabetes and cardiovascular disease later in life. Animal models have demonstrated that increased weight gain in offspring exposed to maternal obesity is usually preceded by increased food intake, implicating altered neuronal control of food intake as a likely area of change. The hypothalamus is the primary site in the brain for maintaining energy homeostasis, which it coordinates by sensing whole body nutrient status and appropriately adjusting parameters including food intake. The development of the hypothalamus is plastic and regulated by metabolic hormones such as leptin, ghrelin and insulin, making it vulnerable to disruption in an obese in utero environment. This review will summarise how the hypothalamus develops, how maternal obesity impacts on structure and function of the hypothalamus in the offspring, and the factors that are altered in an obese in utero environment that may mediate the permanent changes to hypothalamic function in exposed individuals.